Changes in The Flexural Strength Characteristics of Concrete Due To The Effect of Coconut Fiber Addition on Normal Concrete - Darwis, Zulmahdi; Baehaki, Baehaki; Soelarso, Soelarso; Fathonah, Woelandari; Rahma, Midia; Ramadhan, Malik Agung (Jurnal Fondasi, 2025)
Concrete has high compressive strength, long durability, and easy maintenance. Innovation in using waste such as coconut fibers can improve the mechanical quality of concrete, reduce pollution, and provide added economic value. Fiber concrete is commonly used on broad structural elements to overcome expansion shrinkage due to oxidation, temperature, and evaporation. This study aims to determine the effect of the addition of coconut fiber waste and the optimum percentage on the bending strength characteristics of concrete. This research method is an experiment that compares the results of the bending strength test with the consideration of deflection that occurs on the force received from the variation of coconut fibers as much as 0%, 1.75%, 2.25%, and 2.75% of the weight of cement with a coconut fiber length of 65 mm, a planned quality of f'c 20 MPa, and using test specimens measuring 15 cm x 30 cm for cylinders and 15 cm x 15 cm x 60 cm for beams. Based on analysis and discussion, the addition of coconut fibers influences increasing flexural strength for a certain percentage with the addition of coconut fibers as much as 2.25% of the weight of cement showing the best flexural strength value with less deflection produced than other variations of fiber concrete at the same amount of force when charged.